Parishin From Gastrodia Elata Ameliorates Aging Phenotype in Mice in a Gut Microbiota-Related Manner - Zhao, Xinxiu; Zhou, Shixian; Yan, Ren; Gong, Caixia; Gui, Qifeng; Zhang, Qin; Xiang, Lan; Chen, Lufang; Wang, Peixia; Li, Shumin; Yang, Yunmei (Frontiers in Microbiology, 2022)
The physiological and pathological processes that accompany aging can seriously affect the quality of life of the elderly population. Therefore, delaying aging and developing antiaging products have become popular areas of inquiry. Gut microbiota plays an important role in age-related phenotypes. The present study aimed to investigate the antiaging effects and underlying mechanism of parishin, a phenolic glucoside isolated from traditional Chinese medicine Gastrodia elata. Samples from adult (12 weeks), low-dose (10 mg/kg/d) or high-dose (20 mg/kg/d) parishin-treated and untreated aged (19 months) mice were collected to determine blood indicators, gut microbiota and metabolome, and cardiopulmonary histopathological features. The results showed that parishin treatment ameliorates aging-induced cardiopulmonary fibrosis and increase in serum p16Ink4a, GDF15 and IL-6 levels. Furthermore, parishin treatment alleviated dysbiosis in gut microbiota, including altered microbial diversity and the aberrant abundance of opportunistic pathogenic bacteria such as Turicibacter and Erysipelatoclostridium. Gene function prediction and gut metabolome analysis results indicated that the parishin treatment-altered gut microbiota played important roles in sugar, lipid, amino acid and nucleic acid metabolism, and improved gut metabolic disorders in aged mice. In conclusion, the present study provides an experimental basis of potential applications of parishin against aging.